How is indoor air quality during sleep? A review of field studies - Canha, Nuno (2021)
This review aimed to provide an overview of the characterization of indoor air quality (IAQ) during the sleeping period, based only on real-life conditions’ studies where, at least, one air pollutant was considered. Despite the consensual complexity of indoor air, when focusing on sleeping environments, the available scientific literature is still scarce and falls to provide a multipollutant’ characterization of the air-breathing during sleep. This review, following PRISMA’s approach, identified a total of 22 studies that provided insights into how IAQ is during the sleeping period in real life conditions. Most of the studies focused on carbon dioxide (77%), followed by particles (PM2.5, PM10, and ultrafine), and only 18% of the studies focused on pollutants such as carbon monoxide, volatile organic compounds, and formaldehyde. Despite the high heterogeneity between studies (regarding the geographical area, type of surrounding environments, the season of the year, type of dwelling, bedrooms’ ventilation, number of occupants), several air pollutants showed exceedances of the limit values established by guidelines or legislation, indicating that an effort should be made in order to minimize human exposure to air pollutants. For instance, when considering the air quality guideline of the World Health Organisation of 10 µg·m−3 for PM2.5, 86% of studies that focused on this pollutant registered levels above this threshold. Considering that people spend one-third of their day sleeping, exposure during this period may have a significant impact on the daily integrated human exposure, due to the higher amount of exposure time, even if this environment is characterized by lower pollutants’ levels. Improving the current knowledge of air pollutants levels during sleep in different settings, as well as in different countries, will allow improving the accuracy of exposure assessments and will also allow understanding their main drivers and how to tackle them.